“Voces y espejos” de Espido Freire. Hacia una estética de la perversión en el relato especular - Rodriguez, Samuel Rodriguez (Acta Hispanica, 2014)
Espido Freire (Bilbao, 1974) is one of the most interesting authors of contemporary Spanish literature. She has admitted on numerous occasions her preference for tales. “Voces y espejos” belonging to the storybook Juegos míos (2004), is offered as a paradigm of the obsessions that populate her work: the voices and mirrors as inducers of evil. The mise en abyme while splitting the narrator – widely studied by Lucien Dällenbach – permits the author to develop an alter ego what was so beloved by Borges and Cortázar. And here it aims at a hidden voice in us, which is subtle, barely perceptible, but always evil, which is intended to be reflected by the mirror dangerously. This story also presents the particularity of applying a double mise en abyme for its metaliterary character, what refers to the proper conception and reception of the story in a macabre triangle between the author, text and reader.